Based on adaptive modulation laser communication multi-microgrids scheduling system - Chang, Ying; Chang, Dajun; Su, Li (Frontiers in Physics, 2023)
In order to improve the data sharing and comprehensive information processing capabilities between multi-microgrids in the power system, the multi-microgrids scheduling system based on laser communication has been proposed. In order to reduce the error rate of laser communication and reduce the impact of atmospheric turbulence on signal acquisition, an adaptive modulation algorithm has been designed. A mathematical model for laser communication modulation and demodulation based on adaptive modulation algorithm has been constructed. In simulation analysis, the target signal was extracted from the original signal superimposed with atmospheric turbulence noise through filtering and demodulation. The energy fluctuation of the extracted signal decreased from 47.3mV to 5mV. The energy attenuation trend of communication lasers within the range of 0-6km was experimentally tested. Within 2.0km, the energy demodulation results of both algorithms are similar, both below 10%. After exceeding 2.0km, the calculation error of the adaptive modulation algorithm remains basically unchanged, while the error of traditional algorithms increases by about twice. For the APD response value, the adaptive modulation algorithm demodulation has a higher response range concentration ratio and the higher envelope recognition. Under different nominal atmospheric turbulence values, the maximum error rates of the adaptive modulation algorithm are 5.8×10-8, 8.9×10-8, and 1.2×10-7, respectively, while the maximum error rates of the amplitude coherent algorithm are 2.9×10-5, 6.3×10-5, and 1.05×10-4, respectively. It can effectively suppress the impact of atmospheric turbulence on the error rate of laser communication by adaptive modulation algorithm.